Teachers' Competence in Implementing Variations in Learning at SD Negeri 17 Sungai Pinyuh - Syarofah, Syarofah; Yunika Afryaningsih; Dessy Setyowati (Jurnal Pendidikan Indonesia, 2025)
This research aims to (1) describe variations in teaching styles at SD Negeri 17 Sungai Pinyuh (2) describe variations in interactions and activities at SD Negeri 17 Sungai Pinyuh (3) Describe variations in media use at SD Negeri 17 Sungai Pinyuh. To answer the questions above, this research uses a qualitative approach with a descriptive type to obtain in-depth data. Researchers use observation techniques. As for data analysis, researchers used data reduction analysis, data collection, and drawing conclusions/verification. The results of the research show that (1) of the five teachers have used variations in teaching styles well during ongoing learning. in the activity of the teacher providing a variety of clear sounds, in the variation of focusing the teacher's attention using variations of attracting students' attention verbally, in the variation in silence the teacher gives students time to think which makes the students feel bored, in the variation of gaze contact the teacher pays attention to the students, in the variation of member movements The teacher's body is adapted to the learning material and the teacher also puts on an enthusiastic face for the ongoing learning. In various position shifts, the teacher has moved at the base of the target and around the room. (2) the interaction pattern used by the teacher uses 3-way interaction, namely student-student-teacher but there is no interaction between students. (3) of the five teachers, with variations in the use of media, the teachers only focused on learning materials and used teaching aids that were appropriate to the content of the material without any other teaching aids.